Community Service at the "Tabanan Lestari" Farmers Group in Banjar Bugbugan Sari, Senganan Village, Penebel District, Tabanan Regency, Bali - Ida Bagus Komang Mahardika; Made Sri Yuliartini; Anak Agung Ngurah Mayun Wirajaya (Asian Journal of Community Services, 2023)
The solutions offered to overcome the problems faced by the partners are carried out through a community partnership program through farmer assistance, counseling, training, technology transfer, techniques for making biological fertilizer from citrus fruit waste, as well as strengthening group institutions. This Community Service Program is implemented in this farmer group. The method used to achieve this goal is through counseling, training and application of technology with direct practice in the field. The implementation of Community Service has gone well according to plan and the participation and response of all members have been very enthusiastic in its implementation. The output targets are a technology package for managing orange plantation waste into good quality biofertilizer, and strengthening the institutions of integrated agrotourism groups in Senganan village and publishing them in scientific journals.